Negotiating Heritage: The Institutionalisation and Adaptation of Penadhon in Ponorogo - Aling Madani; Johny Alfian Khusyairi; Samidi (Mudra Jurnal Seni Budaya, 2026)
This study examined the impact of traditional art and local community engagement on preserving and conserving Ponorogo's traditional outfit, Penadhon. This traditional outfit is unique as it is used and presence appears both art events, Reyog, and in the official life of the people of Ponorogo. Penadhon Therefore, this article intends to look at the roles of the Ponorogo community as an entity in maintaining and preserving this traditional outfit. The questions posed are on the reasons for the origin of Penadhon and how this clothing became popular. The research for this article applied a qualitative approach. Research data was obtained through interviews and tracing printed sources in the form of documents and photos. The secondary sources used for this research. Secondary sources used in this research include books and articles in both printed and digital form. Through the research process, it was discovered that reviving the use of Penadhon was related to respect for the charismatic figure of Ponorogo in the past, Warok. The method used to popularize the use of Penadhon is through Reyog performances, both annually and temporarily, its use on big holidays in Ponorogo, both of which are supported by the big Penadhon wholesale business that occurs both in Java and outside Java.